(untitled) (Altre Modernità, 2018)
The object of analysis of the present work is Norma Lazo’s essay El silencio en cuatro tiempos, which focuses on the function of the author by means of the literary device of the manuscript composed by an unknown author, as well as the creation of a fictitious author and the reinterpretation and representation of a medieval text, Treaty on the contemplative method in the imploration of the divinity of words and their things, by the apostate Gervasio de la Cruz. A skilful literary game of references and philological quotations that leads us to reflect on the presence or concealment of the author in literature. The text questions writing and its creation in literature, not only in Latin America, but also in Europe: because this is a universal experience. A more in-depth study is dedicated to the parallelism between the first chapter of the book which is the object of this study and Josefina Vicens’ novel, The Empty Book, which is here analysed as the initial and main model employed during the composition of Norma Lazo’s book.